FORMATION OF ELECTORAL RULES: THE CONCEPT OF ELECTORAL ENGINEERING - Макаренко, А.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article deals with the concept of the electoral engineering as a relatively new phenomenon that takes place in the political reality of the representative democracy states. The specificity of the term and approaches to its interpretation are defined. The distinction between manipulation technologies and electoral engineering is analyzed. The factors that should ensure compliance with its use for the national interest, and not for individual groups, are given. The problems and needed directions of electoral engineering in the Ukrainian context are described.